Assessment of the sustainability in dehesa farms according to size and livestock prevalence - Gaspar Garcia, P; Mesias Diaz, F J; Escribano Sanchez, M; Pulido Garcia, F (ITEA-INFORMACION TECNICA ECONOMICA AGRARIA, 2009)
Assessment of the sustainability in dehesa farms according to size and livestock prevalence This paper presents an evaluation of the sustainability of the dehesa livestock systems located in Extremadura (SW Spain). We apply a methodological adaptation of the framework known as MESMIS (Framework for the Evaluation of Management Systems incorporating Sustainability Index). This method is based on the valuation of basic attributes of sustainability using indicators and indices that allow simultaneous and comparative analyses of farms based on their size and productive orientation. A global value of sustainability for each typology present in dehesa is obtained from a fundamentally technical-economic perspective, taking into account some environmental and social aspects. The dimension of the operation influences the capacity of adaptation of operations, with bigger farms showing better adaptability. The smaller farms compensate their management by improving productivity levels. We also observe that the presence of Iberian pig improves the sustainability index of the operations.
Keywords: Dehesa; extensive livestock; farm management; Sustainability indicators

Evaluación de la sostenibilidad en exploraciones de dehesa en función de su tamaño y orientación ganadera - Gaspar Garcia, P; Mesías Díaz, Francisco Javier; Escribano Sánchez, Miguel; Pulido, F (ITEA, información técnica económica agraria, 2009)
Keywords: dehsa; extensive livestock; farm management; Sustainability indicators